Influence of gender inequalities in curative and preventive health care use among children between 2 months to 5 years of age and its impact on changing sex ratio of the community - Agrawal, Avyact; Ashokan, Vishakha (International Journal Of Community Medicine And Public Health, 2023)
Background: Male preferring mentality of the society has created a discrimination against females in seeking curative and preventive health care and their overall nutritional status. Methods: Prospective observational study that included all the children between the age of 2 months to 5 years. The data collection started from January 2020 from registers in a monthly fashion till December 2020 and were analysed and categorized based on sex difference in admissions, leave against medical advice, mortality, immunisation, and follow-up. Results: The basic descriptive statistics shows that there is gross difference in the frequency of admissions in Inpatient (males- 58.33%, females- 41.67%), follow-up care (males- 56.33%, females- 43.67%) and immunization (males-53.06%, females-46.94%). The number of females children who left against medical advice (10.49%) were more than male children (6.45%) and is also statistically significant. In our study a greater number of female deaths (11.02%) occurred compared to males (10.15%) despite of their survival advantage. The number of female children (48.30%) who were admitted in nutritional rehabilitation centre were less compared to the number of males (51.70%). The hospital sex ratio at birth was 114 males per 100 females which is worse than the national average. Conclusions: Male biased community has put females at risk starting from the time of conception. Gender difference is experienced throughout and in all aspects of social, cultural, healthcare fields and nutritional needs.